Literatur Review: Analysis of Essential Oil Secondary Metabolite Content in Several Plants - Noli, Zozy Aneloi; Delfi, Shyla Aulia; Zulkarnain, Alivia; Syabila, Hutri Dinda; Rusiati, Anisa Rahman; Santoso, Putra (Jurnal Biologi Tropis, 2025)
Indonesia’s rich plant biodiversity offers a wide array of secondary metabolites, including essential oils, known for their antioxidant, antifungal, and antibacterial properties. This review article examines the secondary metabolite composition of essential oils from various plant species by synthesizing findings from existing literature. The review article highlights the presence of diverse compounds, including terpenes, phenols, and alkaloids, with variations observed between species—for instance, limonin in citrus, linalool in ylang-ylang, and eugenol in cloves. Commonly utilized methodologies, such as steam distillation and GC-MS analysis, discuss their effectiveness in characterizing essential oil components. The findings underscore the extensive potential of crucial oils for applications in health, food, and cosmetic industries, providing a foundation for future research and practical innovations.